The Impact of Surface Coal Mining on Residential Property Values: A Hedonic Price Analysis - Austin M Williams (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2011)
The use of certain surface mining techniques is currently a heavily-debated environmental issue and one where consideration of non-market values is likely to lead to the creation of better public policy. This study uses the hedonic pricing method to investigate the impact that surface coal mines have on residential property values. The results of this statistical analysis show that as the number of surface mines and their average production increases, the median value of housing units in a county significantly decreases. In particular, for the three model specifications explored, it is estimated that the addition of a surface mine to the average county decreases aggregate property values by between 7,949,363.77 and 40,146,061.87.
Keywords: Coal Mining; Real Estate; Environment